Elution patterns of rubella IgM, IgA, and IgG antibodies from a dextran and an agarose gel. - Pattison, J R (1975)
The elution pattern of serum proteins and the distribution of rubella HAI activity in 95 sera from 65 cases were determined after gel filtration with (a) Sephadex G-200 and (b) Bio-Gel A-5M. Rubella HAI antibody in peak 1 after Sephadex G-200 fractionation of early convalescent sera consists of both IgM and high molecular weight IgA. However, these two classes of antibody can be distinguished by gel filtration with Bio-Gel A-5M. Bearing these differences in mind, the results of fractionation with the two gels correlate very well although the use of Bio-Gel A-5M gives a slightly less sensitive technique for the diagnosis of recent infection.